A Framework of Scalable Layered Access Control for Multimedia - Zhu, Bin Benjamin; Feng, Min; Li, Shipeng (IEEE Int. Symp. Circuits and Systems 2005, 2005)
Scalable coders offer various scalabilities with a single codestream. In this paper, we extend our previous work to propose a general framework to enable a single encrypted scalable multimedia stream to support different access types and different access layers for each access type. Access types are protected orthogonally such that access to one type does not deduce the secret to access to other types. Layers are protected one-directionally such that a higher layer accesses and reuses the data of all the lower layers of the same type but not vice versa. An efficient key scheme is proposed to minimize complexity of key management for the framework. With an appropriate encryption scheme is used, an encrypted stream generated by our proposed framework enables fine granularity of scalability to achieve “encrypting once and decrypting multi-ways”, which is very desired in many DRM applications. The proposed framework works with all scalable coders. This paper describes the detail to work with JPEG 2000 and MPEG-4 FGS.